POTENTIAL OF CARBON SINK IN MANGROVE SUBSTRATES IN LEMBAR BAY, WEST LOMBOK, INDONESIA - Firman Ali Rahman Firman; Dewi Putri Lestari; Alfian Pujian Hadi; Anis Syakiratur Rizki; Aisha Zea Almahyra; Arsya Zafran Alvarendra; Nuzuly Ilmia Cerminand; Nening Listari; R. Didi Kuswara; Zulkarnain Gazali; Maya Ekaningtias; Siti Wardatul Jannah; Baiq Yulia Hasni Pratiwi (BIOTROPIA, 2023)
Mangroves are one of the coastal vegetation that can mitigate carbon (carbon sink and carbon storage). This study aimed to determine the potential for soil carbon stock found under stands of mangroves in Lembar Bay, West Lombok, and West Nusa Tenggara. The research began with the identification of the species and then proceeded toa sampling of the soil, which was then analyzed using the Walkley and Black method. The results showed that there were ten species of mangroves, namely, Rhizophora stylosa, Avicennia lanata, Avicennia marina, Bruguiera gymnorrhiza, Ceriops decandra, Excoecaria agallocha, Lumnitzera racemosa, Scyphiphora hydrophyllacea, Thespesia populnea, and Xylocarpus maluccensis. The highest soil carbon content percentage was found in the lower soil of the A. lanata (1.43 %C) mangrove, and the lowest was found in the lower-stand soil of E. agallocha (0.21 %C). Meanwhile, the carbon sinks per meter were 0.002-0.066 gC/m2, with an average of 0.020±0.020 gC/m2. The estimated total soil carbon sink in 10 mangrove stands was 0.20-6.60 tons C/ha, with an average of 2.18±2.010 tons C/ha. The average total estimated soil carbon stock found in 20.49 ha of the mangrove area studied was 44.67 tonsC, which is equivalent to 263.69 tonsC in a mangrove area of ​​120.96 ha in Lembar Bay.